2018
DOI: 10.3164/jcbn.17-40
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione homeostasis is significantly altered by quercetin via the Keap1/Nrf2 and MAPK signaling pathways in rats

Abstract: Previously, we showed that 0.5% quercetin simultaneously decreased serum homocysteine and glutathione (GSH) levels in rats. The aim of the present study was to investigate the effects of 0.5% quercetin on GSH metabolism, related enzymes and signal pathways in rats. Rats were fed the control diet and 0.5% quercetin-supplemented diet for 6 weeks. The results showed that quercetin reduced serum and hepatic content of GSH and the ratio of GSH and oxidized glutathione (GSSG), enhanced hepatic activity and mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 55 publications
2
22
0
1
Order By: Relevance
“…Thus, the dynamic balance of GSH is produced, which may cause the inhibition of GSH levels in low doses. This inhibition of quercetin on GSH at the level of 0.5% is reported in the literature [16].…”
Section: Antioxidant Activity Of Quercetin In Vivosupporting
confidence: 80%
“…Thus, the dynamic balance of GSH is produced, which may cause the inhibition of GSH levels in low doses. This inhibition of quercetin on GSH at the level of 0.5% is reported in the literature [16].…”
Section: Antioxidant Activity Of Quercetin In Vivosupporting
confidence: 80%
“…In addition, we have recently demonstrated that, the premature aging phenotypes in HGPS hMSCs partially attributes to the repression of NRF2-mediated anti-oxidative response, whereas the reactivation of NRF2 reverses the nuclear defects in HGPS cells and restores their in vivo viability in mice (Fang et al, 2018 ; Kubben et al, 2016 ). Interestingly, Que is reported as an activator of NRF2-mediated anti-oxidative pathway (Bahar et al, 2017 ; Dai et al, 2018 ; Gao et al, 2018 ; Kim et al, 2018 ). Consistently, by RNA-seq analysis we identified that Que upregulated a series of anti-oxidative genes including GSTP1 , GSR and GSTM1 , all of which are NRF2 targets, indicating that Que may exert anti-oxidative effect via the activation of NRF2.…”
Section: Discussionmentioning
confidence: 99%
“…In human aortic endothelial cells, quercetin affects glutathione levels and redox ratio regulation not through oxidation but through the formation and cellular export of quercetin-glutathione conjugates and upregulation of glutamate-cysteine ligase extracellular quercetin-glutathione conjugates [ 30 ]. Furthermore, quercetin alters hepatic GSH metabolism by modulating GSH metabolic enzyme activities via p38, ERK1/2 MAPKs, and Nrf2 pathways in rats [ 31 ]. Studies have demonstrated that polyphenols could reduce dexamethasone-induced muscle atrophy and downregulate muscle atrophy-related proteins such as ubiquitin ligase atrogin-1 and MuRF-1 [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%